2004
DOI: 10.1007/s00330-004-2334-0
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic arterioportal shunting and anomalous venous drainage: understanding the CT features in the liver

Abstract: The increased use of high-contrast volume, arterial-phase studies of the liver has demonstrated the frequent occurrence of arterioportal shunts within both the cirrhotic and non-cirrhotic liver. This article sets out to explain the underlying microcirculatory mechanisms behind these commonly encountered altered perfusion states. Similarly, well-recognised portal perfusion defects occur around the perifalciform and perihilar liver and are largely caused by anomalous venous drainage via the paraumbilical and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
2
22
1
Order By: Relevance
“…This result was not consistent with our previous conclusion in normal rats, which demonstrated that preserving hepatic artery blood did not increase the risk of blood loss significantly [9]. Compared with the normal rat liver, many histologic changes emerged in the cirrhotic rat liver, such as newborn blood vessels in the septa, anastomoses between the portal vein and hepatic artery, and the formation of intrahepatic shunting [28]. Blood coagulation also decreased in cirrhotic rats.…”
Section: Discussioncontrasting
confidence: 74%
“…This result was not consistent with our previous conclusion in normal rats, which demonstrated that preserving hepatic artery blood did not increase the risk of blood loss significantly [9]. Compared with the normal rat liver, many histologic changes emerged in the cirrhotic rat liver, such as newborn blood vessels in the septa, anastomoses between the portal vein and hepatic artery, and the formation of intrahepatic shunting [28]. Blood coagulation also decreased in cirrhotic rats.…”
Section: Discussioncontrasting
confidence: 74%
“…The Zonal pattern seen in four patients (1 with nodules), occurs in response to a chronic reduction in portal venous inflow leading to central zone preservation in the areas of residual portal vein supply [21]. We have previously demonstrated that the zonal pattern is associated with lower hepatic vein pressures and lesser degrees of fibrosis/cirrhosis than that of the reticular pattern in keeping with an earlier phase of the same disease process [4].…”
Section: Discussionmentioning
confidence: 95%
“…The lesion revealed the typical bright, sharp-marginated appearance of the simple cyst (arrow) at T2-weighted turbo spin-echo magnetic resonance (MR imaging) (c, TR/TE, 2,000/150 ms) the heterogeneous microbubble destruction at CEUS and by portal perfusion defects at contrast-enhanced CT. Heterogeneous microbubble destruction is frequently observed at high-transmit power insonation [14], determining focal hypovascular areas that simulate liver metastases. Portal perfusion defects are largely caused by anomalous venous drainage via the paraumbilical and parabiliary venous systems and may be observed at CT [32,33].…”
Section: Discussionmentioning
confidence: 99%